Rise Overrun: Condoization, Gentrification, and the Changing Political Economy of Renting in Toronto - Sean Grisdale; Alan Walks (Urban Planning, 2022)
Privately owned high-rise condominiums have been increasing as a proportion of all housing units built in the Greater Toronto Area for many decades. This has inspired a growing literature theorizing both “condoism” as an emergent planning-development regime and the implications of “condoization” and “condofication” for urban governance and everyday life in cities like Toronto. Building on this literature, this article assesses the implications of Toronto’s increasing reliance on (mainly vertical) condominium development for the socio-spatial transformation of the housing market, particularly for renters. Analyzing time-series data from Canada Mortgage and Housing Corporation and the Census of Canada to quantify the effects of the city’s condoization, we answer three key questions: How important is condominium development for understanding the restructuring of Toronto’s economy? How has condoization contributed to the ongoing gentrification of Toronto’s inner city? How is condoization restructuring Toronto’s rental market? Building on previous research categorizing and mapping the gentrification of Toronto’s inner city, we find that condoization is an increasingly defining element restructuring the city’s rental market, while this restructuring also plays a central role in the advancing gentrification of the city’s core.